Procalcitonin and white blood cell as predictors of urosepsis in urinary tract obstruction patients at Sanglah Hospital Denpasar - Gatot Triwono; Anak Agung Gde Oka; Desy Permatasari; Christopher Ryalino (Indoscholar, 2019)
Introduction: Patients with urinary tract obstruction are often accompanied by urinary tract infections. In some cases, it develops into urosepsis that increases mortality. Early detection capability is essential. The purpose of this study was to determine the role of serum procalcitonin (PCT), nitrite urine (NU) and white blood cell (WBC) as urosepsis predictors in patients with urinary obstruction. Methods: This is a cross-sectional study involving 36 samples carried out at our hospital using consecutive sampling technique from December 2016 to February 2017. Statistical analyses used were a bivariate test and multivariate test using Poisson regression. Results: From the bivariate test analysis, serum PCT level of ≥0.25 ng/ml, positive result for NU, and a WBC amount of ≥12,000 cells/mm3 were predictors for urosepsis. In the multivariate test, we obtained a PCT serum level of ≥0.25 ng/ml, and WBC of ≥12,000 cells/mm3 were true predictors of urosepsis in patients with urinary tract obstructions with infections. Conclusion: Serum PCT and WBC can be used as a predictor of urosepsis in patients with urinary tract obstruction.